Language Anxiety Among English Foreign Language Learners - Bintang Zul Hulaifah, Nur; F. B. Sibuea, Todo (KnE Social Sciences, 2023)
The purpose of this study was to find out how much language anxiety EFL university students have, what causes it, and how they deal with it. This study aims to fill a gap in the literature regarding the causes of language anxiety, the causes, and how people cope with it, as most researchers have not yet combined those three factors into a single study. The current study used a mixed method,a questionnaire and a semi-structured interview were used. FLCAS was used as a questionnaire to collect quantitative data. At the same time, questionnaires and semi-structured interviews were used to select the qualitative method. This study included 40 male and female EFL university students from the Faculty of Business and Social Sciences at one of Jakarta’s private universities. Their ages range from 18 to 25 years. In this study, the questionnaire items revealed two levels of anxiety: 1) low anxiety (62%) and 2) moderate anxiety (38%). Three causes of language anxiety were identified using a combination of questionnaire items and semi-structured interviews: 1) Inadequate confidence in speaking English in class; 2) Fear of making mistakes when speaking English; and 3) Lack of vocabulary/grammar knowledge. Keywords: foreign language anxiety, speaking anxiety, FLCAS, level of anxiety, causes of anxiety